A Multi-Criteria Decision-Making Approach for Warehouse Location Selection using TOPSIS - Ira Modifa Tarigan; Muhammad Ade Kurnia Harahap; Endang setyawati; Jimmy Moedjahedy; Ernie C Avila; Robbi Rahim (PT Mattawang Mediatama Solution, 2023)
This research makes use of the Method for Order of Preference by Similarity to Ideal Solution, also known as the TOPSIS approach, in order to discover the most suitable site for a company's warehouse. Following the establishment of the criteria for the selection of the warehouse location, weights were allotted to each of the criteria. The min-max method was utilized to do data normalization once it had been collected for each prospective location. After constructing the decision matrix with the weighted normalized values and determining the ideal and non-ideal solutions for each criterion, the results were then presented. Following the calculation of the Euclidean distance between each potential location and the ideal and non-ideal solutions, the TOPSIS formula was used to determine the relative proximity between each of the potential locations. The site of the potential location that was the highest relative closeness to the optimum solution was chosen to be the optimal location for the warehouse. By employing this strategy, the company will be able to make an educated decision regarding the location of their warehouse, which will, in the long run, result in improved operational efficiency and cost savings.